Activation of the canonical Wnt/β-catenin pathway in ATF3-induced mammary tumors. - Leqin Yan; Luis Della Coletta; K Leslie Powell; Jianjun Shen; Howard Thames; C Marcelo Aldaz; Michael C MacLeod (PLoS ONE, 2011)
Female transgenic mice that constitutively overexpress the transcription factor ATF3 in the basal epithelium of the mammary gland develop mammary carcinomas with high frequency, but only if allowed to mate and raise pups early in life. This transgenic mouse model system reproduces some features of human breast cancer in that about 20% of human breast tumor specimens exhibit overexpression of ATF3 in the tumor cells. The ATF3-induced mouse tumors are phenotypically similar to mammary tumors induced by overexpression of activating Wnt/β-catenin pathway genes. We now show that the Wnt/β-catenin pathway is indeed activated in ATF3-induced tumors. β-catenin is transcriptionally up-regulated in the tumors, and high levels of nuclear β-catenin are seen in tumor cells. A reporter gene for Wnt/β-catenin pathway activity, TOPGAL, is up-regulated in the tumors and several downstream targets of Wnt signaling, including Ccnd1, Jun, Axin2 and Dkk4, are also expressed at higher levels in ATF3-induced tumors compared to mammary glands of transgenic females. Several positive-acting ligands for this pathway, including Wnt3, Wnt3a, Wnt7b, and Wnt5a, are significantly overexpressed in tumor tissue, and mRNA for Wnt3 is about 5-fold more abundant in transgenic mammary tissue than in non-transgenic mammary tissue. Two known transcriptional targets of ATF3, Snai1 and Snai2, are also overexpressed in the tumors, and Snail and Slug proteins are found to be located primarily in the nuclei of tumor cells. In vitro knockdown of Atf3 expression results in significant decreases in expression of Wnt7b, Tcf7, Snai2 and Jun, suggesting that these genes may be direct transcriptional targets of ATF3 protein. By chromatin immunoprecipitation analysis, both ATF3 and JUN proteins appear to bind to a particular subclass of AP-1 sites upstream of the transcriptional start sites of each of these genes.